Beyond paradise. Series three [videorecording (DVD)] - Thorogood, Robert; Jordan, Tony, 1957- (BBC, 2025)
DI Humphrey Goodman and his fiancee Martha juggle the demands of their life in Devon. The Shipton Abbott team solve more intriguing crimes including a body found in the river on the county border, a baffling chocolate box poisoning, a historic farming feud and a spiking incident on the water. Away from the police station, Martha and Humphrey try to overcome unexpected hurdles as foster parents, while the reappearance of Martha₂s old flame Archie presents an unexpected challenge.